PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL MODERATING (STUDI PADA PT. RANDUGARUT PLASTIC INDONESIA) - Pitra Yusuf Aditya; Rini Nugraheni (Faculty of Economics and Business Diponegoro University, 2014)
This experience aims to detect motivation influence towards employee performance withorganization culture as variable moderating (case study pt. randugarut plastic indonesia.sample that chosen to use census method or population watchfulness, where entirepopulation members that be all production part employees at pt. randugarut plasticindonesia is taken as watchfulness sample or respondent. this sample election threatensin opinion suharsini arikunto (2002) that when does population total less than 100 bettertaken all as watchfulness sample so that got sample 80 respondents.This experience method uses multiple linear regression test with a few data analysismethod which is validity test, reliability test, normality test, multikoleniarity test,heterokedastisitas test. multiple linear regression test, simultaneous test, determinationcoefficient test, and test t (hypothesis test).Testing result by using multiple linear regression shows the influential of motivationtowards employee performance in PT. Randugarut Plastic Indonesia.The interactionbetween motivation towards employee performance with organization culture as variablemoderating shows that motivation influenced employee performance. By those finding therecommendation for company are increasing employee motivation, paying attention foremployee safe taste in work, or company can give team cooperation in work, give freeemployee innovates in work in PT. Randugarut Plastic Indonesia.Keyword: motivation, organization culture, and employee performance